Quality of life in transplanted renal that consulted in an institution of health in Medellin, Colombia - Montoya Hincapié, Sandra M.; Paja Becoche, Ruby M.; Salas Zapata, Carolina (Universidad y Salud, 2017)
Introduction: Renal transplantation performed on patients with chronic renal disease (CRD) stage five, is an alternative treatment that prolongs survival, reduces morbidity, accelerate social and medical rehabilitation. However it is necessary to carry out studies to evaluate the quality of life of these patients. Objective: Establishing the socio-demographic, clinical and service characteristics of the health insurer that explain the life quality of kidney transplanted patients who consulted a health institution in Medellin in 2016. Materials and methods: Quantitative and transversal survey carried out in 228 patients to whom the SF-36 instrument were applied. There were calculated the statistical tests of Kolmogorov Smirnov for normality, U de Mann Whitney, Kruskal Wallis and the Spearman correlation coefficient. In the multivariate analysis the median regression model was selected. Results: 50% of the patients got 83.3 or less in its life quality score. The multivariate regression model shown significant differences in the time variables after transplantation and readmission to hospital in the last year; by each readmission to hospital, the values of life quality decreased in 3.82 points; according to the time after the transplantation, it was found that going from a state where the patient has a term between 7 and 36 months, to a state where the patient has a term over 36 months, shown a decrease of 12.03 points in life quality, adjusted by the other variables. Conclusions: The variables that best explained the life quality of the kidney transplanted patients who consulted a health institution were the time of transplantation and the number of readmissions to hospital.